Laser ablation synthesis of new gold tellurides using tellurium and nanogold as precursors. Laser desorption ionisation time-of-flight mass spectrometry - Svihlová, Katarína; Prokeš, Lubomír; Skácelová, Dana; Peña-Méndez, Eladia María; Havel, Josef (Rapid communications in mass spectrometry, 2013)
RATIONALE: Only a few gold tellurides are known. However, Laser Ablation Synthesis (LAS) using Laser Desorption Ionisation (LDI) time-of-flight mass spectrometry (TOF MS) has high potential for the generation of new compounds. METHODS: LDI of nanogold-Te conjugate using a nitrogen laser 337 nm was applied while the mass spectra were recorded in positive and negative ion modes using a quadrupole ion trap-TOF mass spectrometer equipped with a reflectron. Diffuse coplanar surface barrier discharge was applied for the plasma treatment of glass and silicon surfaces. RESULTS: A form of nanogold-Te conjugate was prepared and found suitable for LAS of gold tellurides. Several new Au(m)Te(n) (m = 1-11; n = 1-4) clusters were identified. An excess of nanogold and chloride or an excess of auric acid caused the formation of mixed Au(m)Te(n)Cl(x) clusters. The nanogold-Te conjugate can be deposited from an aqueous suspension onto glass while the deposition is strongly enhanced if the surface is modified by plasma. CONCLUSIONS: LDI of nanogold-Te conjugate is a suitable procedure for the generation of new gold telluride clusters. Treatment of borosilicate glass with a diffuse coplanar surface barrier discharge strongly enhances the deposition of gold tellurides on glass while limited adsorption on a silicon surface was observed.